К вопросу создания и реализации концепции взаимодействия органов и учреждений здравоохранения железнодорожного транспорта государств-участников СНГ - Анашкин, В.В.; Волкова, А.С. (Актуальні проблеми транспортної медицини, 2005)
A railway transport takes leading seat in the transporting complex of the states-participants CIS, development of transcontinental connections, acceleration of economic and social development of countries. In this connection the role of the concerted actions of railways administrations of states - participants of CIS in area of health protection, above all things, hygienical and epidemiology accompaniment of transformations on a transport is promotion. Conception of co¬operation of organs and establishments of health protection of railway transport of the states of Concord is offered in the article.